DEVELOPMENT OF THE COMPETENCE OF THE SCIENCE OF TECHNOLOGY - Kholikov Otabek Siddiqjonovich; Kholmirzaeva Dilafruz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this scientific article explains the content of the development of software for general and specialized science classes in the development of knowledge and skills of the future teacher of technology science. It is covered that software learning tools are one of the promising forms of increasing the effectiveness of the educational process.